Urban territorial formation and management of wasteland in Rondonópolis-MT - Rodrigues, Jairoeidi Neves; Negri, Sergio Sebastião (National Journal of City Management, 2023)
The use and form of land occupation can occur in diverse ways, in line with the interests of those in power of the formation of these spaces. Creating urban spaces involves designing and constructing areas within cities that result in landscapes reflecting on the social disparities due to their organization and occupation. Urban voids represent a widespread phenomenon in many Brazilian cities and are one of the main tools for controlling and privatizing land for future gains from exploiting urban land. The urban voids phenomenon has various effects on the management and territorial control of the city. Unused land should be used for social purposes. It often leads to several social problems, including the lack of maintenance and partial abandonment. By taking a comprehensive approach, we can effectively tackle these challenges and find successful solutions. Therefore, this work aims to analyze the wastelands present in the urban space of Rondonópolis and to understand the factors that allow for the maintenance of large wastelands in the eastern area of Rondonópolis. This study employed bibliographical research using theses, dissertations, and scientific articles, as well as the analysis and interpretation of municipal urban management laws, field research, and the analysis and interpretation of satellite images. It is necessary to take an innovative approach to the management and occupation of wastelands in Rondonópolis in order to solve the problem of their existence and ensure that they fulfill their social function.